Factors Predicting Adherence to Dual Antiplatelet Medications among Patients with Acute Coronary Syndrome after Percutaneous Coronary Intervention - Boonkua, Chakariya; Wattanakitkrileart, Doungrut; Sriprasong, Sarinrut; Dumavibhat, Chatkanok (Nursing Science Journal of Thailand, 2022)
Purpose: This study aimed to examine the predictive power of perceived severity of disease, barriers to receive treatment, complexity of medication regimen and medication knowledge on the adherence to dual antiplatelet medications among patients with acute coronary syndrome at post percutaneous coronary intervention. Design: Correlational predictive research design. Methods: The sample consisted of 134 patients with acute coronary syndrome after percutaneous coronary intervention at least one month, and having a treatment plan of using dual antiplatelet for at least one year. Data were collected at the heart and medicine clinics of a tertiary hospital in Bangkok using demographic characteristics questionnaire, Hill-Bone Medication Adherence Korean scale, Perceived Severity of Disease Questionnaire, Barriers to Receive Treatment Questionnaire, The Medication Regimen Complexity Index, and Dual Antiplatelet Knowledge Questionnaire. Descriptive statistics and logistic regression analysis were used for the analysis. Main findings: The finding revealed that 77.6% of the participants were male with mean age of 60.9 years (SD = 12.8). Taking aspirin with brilinta/ticagrelor 56.7%, aspirin with apolets/plavix/clopidogrel 43.3%. Seventy-four point six percent of the sample had high level of dual antiplatelet medications adherence. Perceived severity of disease, barriers to receive treatment, complexity of medication regimen and medication knowledge could together predict the adherence to dual antiplatelet medications among patients with ACS after the intervention by 13.1%. Finally, high level of perceived severity of disease and good level of medication knowledge could significantly predict the adherence to dual antiplatelet medications (OR = .37, 95%CI [.15, .92], p = .034; OR = 3.82, 95%CI [1.07, 13.58], p = .038, respectively). Conclusion and recommendations: High level of perceived severity of disease and good level of medication knowledge affects the adherence to dual antiplatelet medications. Nurses should give advice about the severity of ACS and knowledge on dual antiplatelet medications to improve the adherence.